Melatonin can be, more effective than N-acetylcysteine, protecting acute lung injury induced by intestinal ischemia-reperfusion in rat model - Leite, Alberto Andrade; Reiter, Russel Joseph; Mendes Brandao, Julio Cezar; Sakae, Thiago Mamoru; Marinho, Marcia [UNESP]; Camargo, Celia Regina; Oliveira-Junior, Itamar Souza (Hospital Clinicas, Univ Sao Paulo, 2021)
OBJECTIVES: The current study compared the impact of pretreatment with melatonin and N-acetylcysteine (NAC) on the prevention of rat lung damage following intestinal ischemia-reperfusion (iIR). METHODS: Twenty-eight Wistar rats were subjected to intestinal ischemia induced by a 60 min occlusion of the superior mesenteric artery, followed by reperfusion for 120 min. Animals were divided into the following groups (n=7 per group): sham, only abdominal incision; SS+iIR, pretreated with saline solution and iIR; NAC+iIR, pretreated with NAC (20 mg/kg) and iIR; MEL+iIR, pretreated with melatonin (20 mg/kg) and iIR. Oxidative stress and inflammatory mediators were measured and histological analyses were performed in the lung tissues. RESULTS: Data showed a reduction in malondialdehyde (MDA), myeloperoxidase (MPO), and TNF-alpha in the animals pretreated with NAC or MEL when compared to those treated with SS+iIR (p<0.05). An increase in superoxide dismutase (SOD) levels in the NAC- and MEL-pretreated animals as compared to the SS+iIR group (34 +/- 8 U/g of tissue; p<0.05) was also observed. TNF-alpha levels were lower in the MEL+iIR group (91 +/- 5 pg/mL) than in the NAC+iIR group (101 +/- 6 pg/mL). Histological analysis demonstrated a higher lung lesion score in the SS+iIR group than in the pretreated groups. CONCLUSION: Both agents individually provided tissue protective effect against intestinal IR-induced lung injury, but melatonin was more effective in ameliorating the parameters analyzed in this study.
Keywords: Melatonin; Intestinal Ischemia-Reperfusion; NAC; Acute Respiratory Distress Syndrome; Experimental Model